نماز جنازہ سے متعلق صحابہ کرام کی معمول بہا احادیث پر حافظ زبیرزئی کے اعتراضات کاتنقیدی جائزہ: A critical review of Hafiz Zubair zai's objections to the Sahaabah's routine Baha'i hadiths regarding the funeral prayer - Dr.Mufti Hafiz Ali Nawaz; Dr.Hafiz.M.Mudassar Shafique; Dr.Shahnawaz (Al Manhal Research Journal, 2023)
As a source of Islamic law, the word hadith does not need much introduction in scholarly circles, it has always been of fundamental importance in Islam and significant work has been done on this subject in ancient and modern times. In Islamic sciences, reference is made only to the hadith and the sanad of jurisprudence is taken from the hadith itself and the truth is that no subject of Islam is complete without knowing it. Due to the multiplicity of conquests, when Islam began to spread in different tribes and remote areas, the Companions settled in different places. As a result, there was a shortage of people with knowledge of hadith. Gradually, falsehoods began to spread against the truth. People started fabricating hadiths for their own purposes and attributing it to the Holy Prophet (PBUH). In condemnation of virtue and opponents, to please the kings and careless speakers will start fabricating hadiths to add color to their speeches. With time, some people also denied the hadiths and some raised objections to these hadiths which were based on the daily routines of the Companions of prophet. One of them is Hafiz Zubair Ali Zai who objected to the daily hadiths related to the Companions of prophet. In this article, a scholarly answer has been given to these objections regarding Ahadith.